Simulation and sequential operation analysis of a robotic cell - Ismail, Ahmad Rasdan; Makhtar, Nor Kamilah; Hassan, Azmi; Ismail, Napsiah (2005)
The use of robotics has enjoyed increasing popularity among manufacturers. To be competitive, every area of manufacturing must be coordinated in a highly integrated but flexible environment. Robotics offers a technology with which the integration of related activities as well as the flexibility to adapt to product changes can be achieved. In this paper, a robotic cell is developed using GRASP2000 software according to the real world scenario of production. The model consists of CNC milling machine, CNC lathe machine, conveyor system (roller type) and racking shelves. The simulation is conducted to show the overall process involved in this robotic cell. Then the sequential operation analysis is conducted to get the feasible optimum cycle time to complete a set of manufacturing operation task. The sequential operation analysis reveals that the total robot cycle time is equal to the total system cycle time for a set of manufacturing operation.